DIFFERENTIAL DIAGNOSIS FOR NORMOTENSIVE HYDROCEPHALUS SYNDROME - S. A. Zhade; E. R. Kharshudyan; E. I. Zyablova; V. V. Tkachev; G. G. Muzlaev (Инновационная медицина Кубани)
Normotensive hydrocephalus is a complex with symptoms including the following triad: walking disturbance, dementia and incontinence of urine. Existence of the specified disorders brings patients to physicians of various specialties. Knowing special features of normotensive hydrocephalus manifestation, well-timed and correctly carried out diagnosis allows to avoid disease advancement and gives chance to this group of patients to improve life quality carrying out a neurosurgical intervention. We present two clinical observations on the basis of which the differential diagnosis for normotensive hydrocephalus is carried out. The literary review of examination technique, diagnostic criteria and approaches to surgical treatment for these patients is offered in discussions.